Rutin Prevents High Glucose-Induced Renal Glomerular Endothelial Hyperpermeability by Inhibiting the ROS/Rhoa/ROCK Signaling Pathway - Wang, Xiaoming; Zhao, Xiaohong; Feng, Ting; Jin, Gang; Li, Zhenjiang (Planta Medica, 2016)
Diabetic nephropathy is a progressive kidney disease caused by damage to the capillaries in the glomeruli. Endothelial dysfunction is an early sign of diabetic cardiovascular disease and may contribute to progressive diabetic nephropathy. Hyperglycemia-induced endothelial hyperpermeability is crucial to diabetic nephropathy. Rutin has beneficial effects on diabetic nephropathy, but the exact mechanisms of its protective effect remain elusive. The aim of this study was to assess the role of pretreatment with rutin in an in vitro model of hyperglycemia-induced barrier dysfunction in human renal glomerular endothelial cells. Human renal glomerular endothelial cells were exposed to rutin and/or hyperglycemia for 24 h. Hyperglycemia increased permeability and decreased the junction protein occludin in the cell-cell junction area and the total expression in human renal glomerular endothelial cells, whereas rutin treatment significantly corrected these abnormalities. Furthermore, hyperglycemia-induced activation of RhoA/ROCK was reversed by treatment with rutin or the knockdown of ROCK2. Interestingly, rutin prevented hyperglycemia-induced hyperpermeability, and dysfunction of the tight junction, a high level of reactive oxygen species, and activation of RhoA/ROCK were significantly abolished with the knockdown of Nrf2. In conclusion, rutin significantly prevented hyperglycemia-disrupted renal endothelial barrier function by inhibiting the RhoA/ROCK signaling pathway through decreasing reactive oxygen species, which was mediated by the activation of Nrf2. Our results may explain, at least in part, some beneficial effects of rutin that may be applicable to the treatment of vascular disorders in diabetic nephropathy.
Keywords: rutin; high glucose; renal glomerular endothelial permeability; RhoA/ROCK; Nrf2/ROS